Aging and social vulnerability in the State of Mexico, 2010 - Montoya-Arce, Bernardino Jaciel; Román-Sánchez, Yuliana Gabriela; Gaxiola-Robles Linares, Sergio Cuauhtémoc; Montes-de Oca Vargas, Hugo (Papeles de Población; Vol. 22 Núm. 90 (2016), 2018)
The issue of the people who are aged 60 or more is among the imperative social worries; that is to say that in demographic terms they have been lucky to reach old age. In Mexico, the State of Mexico is the state which has the highest number of population who are aged 60 or more, which exceeds the 1.2 million people in 2010. The figure itself strikes the most, which is why it is proposed to analyze how their life is and what the individuals in their daily lives are exposed to, how exposed they are to risks and how able they are to avoid them, since risks, dependency, and their limited capacities place them in situations of social and personal vulnerability. In this scenario, the objective of this article is to identify the level of social vulnerability senior citizens in the State of Mexico face at municipality level. In order to achieve this, a rate of social vulnerability of the elderly people in the municipalities of the State of Mexico was estimated through the principal components methodology. The data comes from the 2010 Census of Population and Housing. The findings suggest that senior citizens face diverse situations of social vulnerability which differentially have an impact on their living conditions in the municipalities of the State of Mexico.